Development of Edu Agrotourism Park in Sumilir Valley to Optimize Local Potential of Kemuning Village - Kurniati, Rina; Wungo, Grandy Loranessa; Fitria, Shoimatul; Al Haddad , Dilhya Alfadhil Umar (Warta LPM, 2025)
Kemuning Village holds significant tourism potential with various attractions capable of drawing visitors. Agricultural tourism has emerged as a key development area, with Lembah Sumilir standing out for its breathtaking natural beauty, including views from the foothills of Mount Lawu and the scenic tea plantations However, limited infrastructure and undeveloped attractions hinder its optimization. The need to optimize attractions, amenities, and accessibility at Lembah Sumilir prompted the P3M Community Service Team of Diponegoro University to assist in the preparation of a master plan for Lembah Sumilir Tourism, aimed at providing insights into tourism and its management. Methods include socialization, FGDs, and design finalization. This study formulates a master plan adopting the Edu Agrotourism Park concept, an approach that integrates tourism and agricultural education by leveraging the natural and agricultural wealth of Kemuning Village. The development will focus on seven zones: Tea Education, View Tracking, Glamping & Camping, Mini River Tubing, Slides, Selfie Spots, and Amenities. The P3M community service program is expected to develop Kemuning Village into a self-reliant community by enhancing the welfare of its residents in environmental, social, cultural, and economic aspects, while also fulfilling the hopes and aspirations of the Kemuning Village community, who are actively involved in every stage of the program's implementation.